Practical generalized finite-time synchronization of duplex networks with quantized and delayed couplings via intermittent control - Yang, Ting; Cao, Li; Zhang, Wanli (AIMS mathematics, 2024)
This paper investigates the practical generalized finite-time synchronization (PGFETS) of duplex networks with quantized and delayed couplings. Given that continuous transmission of signals will increase the load and cost of communication, we introduce quantized couplings in the model. Then, via the theorem of finite-time stability, the PGFETS is proposed based on the fact that PGFETS is much more extensive and practical than classical finite-time synchronization. Some sufficient criteria are formulated to achieve the goal of synchronization by utilizing quantized intermittent control schemes. Lastly, the validity of the theoretical results is illustrated by numerical simulations.